DETERMINATION OF HEAVY METALS IN SLIMMING TEAS FOUND IN ZARIA USING ATOMIC ABSORPTION SPECTROMETRY - Vatsa, Muhammad Abdullahi; Bello, I. A.; Garba, N. N.; Soje, A. A.; Abbas, A. M.; Suleiman, A. (FUDMA JOURNAL OF SCIENCES, 2025)
Heavy metals such as cadmium (Cd), lead (Pb), copper (Cu), iron (Fe), and zinc (Zn) pose significant health risks when present in food or herbal products due to their toxicity and cumulative nature. This study aimed to determine the concentration of selected heavy metals in commercially available slimming teas in Zaria, Nigeria, using validated atomic absorption spectrometry (AAS). Four popular tea brands were collected using systematic random sampling. Samples were digested with aqua regia and analyzed via flame AAS (for Zn, Fe, Cu) and graphite furnace AAS (for Pb, Cd). Mean concentrations (ppm) were Cu: 0.0001; Cd: 0.0043; Pb: 0.1218; Fe: 0.3023; Zn: 0.0037. All values were below WHO limits except for Fe, which slightly exceeded the permissible level in two samples. Standard deviation and method validation (LOD/LOQ, recovery rates, and blank controls) were reported. Results suggest potential chronic health implications from cumulative exposure, underscoring the need for regulatory monitoring of herbal slimming products.